A linguística de corpus e os seriados Seinfeld e Friends como base para o ensino de verbos frasais e verbos preposicionados para alunos de língua lnglesa - Rampazzi, Elaine (2008)
The aim of this research was to create activities that can aid the development of the oral fluency of English students of language institutes through Corpus Linguistics analysis. In that regard, the research aimed at finding which are the most frequently phrasal verbs and verbal associations in the oral speech as well as its most typical lexical patterns - to help teachers in preparing material Hence, the main theoretical underpinning for the present study was provided by Corpus Linguistics, which can be defined as a field of Linguistic study concerned with collecting and analysing corpora, which are collections of electronic texts that have been carefully collected for linguistic research. Three corpora have been used in this study. The main corpus is composed by all the episodes of the ten seasons of the sitcom Friends and the nine seasons of the sitcom Seinfeld, made up of 1.622.991 words. The reference corpus contains the oral component of the British National Corpus (BNC), amounting to 4,335,731 words. The research questions pursued in this study aimed at identifying, in the corpora, the most frequent phrasal verbs and prepositional verbs used in oral speech as well as the its most frequent lexicogrammatical patterns. The results of the analysis made it possible to select the terms and its lexicogrammatical patterns to be included in the activities suggested at the end of chapter three. This study will hopefully have made a creative contribution to the existing body of Corpus Linguistics research, more specifically in the area of EFL teaching, as it provides a practical use of Corpus Linguistics and its tools in English Language Teaching and proposes classroom activities based on an oral and audiovisual corpus, seeking to provide the EFL classroom with more enjoyment and efficiency